Reconceptualizing Gratitude in the Digital Age: An Integrative Review of Subjective Well-Being and Online Interventions - Ilham La Jamri,; Haerani Nur (Journal of Applied Health Management and Technology, 2025)
This integrative review aims to synthesize the literature from 2015–2025 to analyze changes in practice and the effectiveness of digitally mediated gratitude interventions. This study uses an integrative review approach by synthesizing 21 selected studies that align with the PRISMA guidelines. The analysis focuses on digital gratitude expressions, evidence of effectiveness, and factors influencing online interventions. The review identifies three main findings: (1) The emergence of various digital gratitude expressions (e.g., personal journaling apps to social media posts). (2) Strong randomized controlled trial evidence indicates that digital gratitude interventions significantly improve subjective well-being, often through reducing negative thoughts. (3) Intervention effectiveness is influenced by design features such as guidance, task variation, and the integration of Artificial Intelligence (AI). This study proposes a reconceptualization of gratitude in the digital age as a multifaceted phenomenon, encompassing new dimensions such as performative, archived, and mediated gratitude. This conceptualization has important implications for positive psychology theory and the design of future digital interventions. Keywords: Gratitude, Digital, Online Interventions, Subjective Well-Being, Reconceptualization